Integrated Ruminant Feeding Systems Utilizing Agro-Industrial By-Products Through Elephant Grass-Based Silage - Azhary, Ahmad; Munir; Semaun, Rahmawati (Integrated and Sustainable Agriculture, 2024)
Integrated ruminant feeding systems utilizing agro-industrial by-products offer a sustainable solution to feed constraints in tropical livestock production. This study evaluated the physical quality and fermentation characteristics of elephant grass–based complete feed silage formulated with different proportions of tofu by-product and rice bran. A completely randomized design with four silage formulations was applied. Silage was anaerobically fermented for 21 days and assessed for organoleptic properties (aroma, color, texture, and fungal growth) and pH value. The results showed that silage formulation did not significantly affect aroma, texture, or pH (P>0.05), with all treatments exhibiting characteristics of good-quality silage, including a pleasant acidic aroma, compact texture, and acceptable pH values ranging from 3.93 to 4.50. In contrast, fungal growth and color were significantly influenced by treatment (P<0.01). Increasing the proportion of rice bran reduced fungal growth and improved silage color, indicating enhanced fermentation stability. The formulation with the highest rice bran proportion demonstrated the most favorable overall silage quality. In conclusion, elephant grass–based complete feed silage integrated with agro-industrial by-products can produce stable and high-quality silage. These findings support the development of integrated and sustainable ruminant feeding strategies that improve resource efficiency and promote circular agriculture.